Composite diaphragm for solid-state lithium-ion battery and preparation method thereof, and solid-state lithium-ion battery
By using composite separators in lithium-ion batteries, the first coating, the first base film layer, the intermediate lithium layer and the second coating of the laminated structure, the problems of low energy density, short cycle life and poor safety are solved, and the battery is realized. Improves energy density and prolongs cycle life, while improving battery safety.
Patent Information
- Application Number
- CN202411162721.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-08-23
AI Technical Summary
Existing lithium-ion batteries have technical bottlenecks in improving energy density, extending cycle life and improving safety, especially inability to take into account battery cycle life, safety and power characteristics.
A composite separator is used, including a first coating, a first base film layer, an intermediate lithium layer and a second coating layer stacked in sequence, the first coating and the second coating layer contain a lithium-containing material, and the intermediate lithium layer is used to supplement the negative electrode activity. The irreversible lithium loss of the substance, the first base film and the second base film serve as a supporting role, reducing the battery impedance and improving the cycle life.
While increasing the energy density of the battery, it reduces the battery impedance, extends the cycle life, and improves the safety of the battery.
Smart Images

Figure CN118693462B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries and relates to a composite diaphragm for a solid-state lithium ion battery and a preparation method thereof and a solid-state lithium ion battery. Background Art
[0002] Lithium-ion batteries have been widely used in mobile phones, notebooks, tablet computers, electric vehicles, electric bicycles, electric buses, industrial and household energy storage, aerospace and other fields due to their high energy density, long cycle life and no memory effect.
[0003] Different application scenarios have different requirements for the main indicators of batteries, but in general, we hope to continuously improve the battery's specific energy, energy density, fast charging, power density, low-temperature discharge, high-temperature storage, high-temperature cycle, floating charge, intermittent cycle, pulse discharge, low cost, and environmental friendliness while ensuring battery safety.
[0004] In order to further meet users' increased requirements for battery life, standby time and usage time, while eliminating battery safety risks, it is necessary to develop battery technology with higher energy density, longer cycle life and better safety.
[0005] The existing technical solutions for improving battery energy density, improving safety, and extending cycle life mainly include: (1) using new high-energy-density electrode materials, such as silicon-based negative electrode materials (CN101740747A) or lithium-rich positive electrode materials (CN116598501A); (2) fine-tuning the battery structure (CN118063975A), reducing ineffective space and weight, and using lightweight materials to make battery shells; by optimizing the cell layout, increasing the heat dissipation structure and other measures, reducing internal stress and heat accumulation, and improving the stability and durability of the battery during operation; (3) using new electrolytes (CN115275473A), such as solid electrolytes instead of traditional liquid electrolytes, to reduce the loss of electrolyte during the cycle and improve the battery's cyclability and safety; (4) introducing a battery management system (CN113733978A) to monitor and control the battery's operating status in real time. By optimizing the charging and discharging strategy and adjusting the operating temperature of the battery, overcharging and over-discharging can be reduced, ensuring that the battery operates in the best condition, thereby improving its actual energy utilization rate and extending the battery cycle life; (5) Adopting a multi-layer structure design (CN115360449A), multiple batteries are stacked to form a multi-layer structure. High-efficiency heat insulation and conductive materials can be used between each layer of batteries to reduce energy loss and increase the overall energy density.
[0006] Although the above technical solutions have solved some technical bottlenecks of battery performance to a certain extent, they have also introduced new or more difficult to solve technical problems.
[0007] For example, in the prior art, the energy density of the battery can be improved by introducing a silicon negative electrode or a lithium-rich positive electrode material. However, the expansion rate of the silicon negative electrode is high, the particles are easily pulverized after cycling, and the electrolyte is continuously consumed. The lithium-rich positive electrode has low energy efficiency and poor kinetic performance. Therefore, the above technical solutions cannot take into account the battery cycle life, safety and power characteristics.
[0008] For another example, fine-tuning the battery structure, introducing a battery management system, and designing a multi-layer structure, such as lightweighting and optimizing the spatial structure, are all auxiliary technical solutions. Although to a certain extent, the battery energy density and cycle life can be improved through external means, there is no technological innovation of the battery from the perspective of the characteristics of the battery cell itself and the intrinsic characteristics of the battery material. It cannot solve the intrinsic safety problem, nor can it effectively improve the battery's energy density and life.
[0009] Another example is the introduction of solid electrolytes to replace existing liquid electrolytes, thereby improving battery safety. Although solid electrolytes have high intrinsic thermal safety, their density is greater than that of existing liquid electrolytes. The introduction of solid electrolytes will significantly reduce the energy density of the battery. At the same time, solid electrolytes do not have the good wettability of liquid electrolytes, so the electrical contact with the electrode material is poor, resulting in poor power characteristics of the battery.
[0010] Therefore, developing a new material and battery technology to comprehensively solve technical bottlenecks such as low battery energy density, short cycle life, poor safety, and poor power characteristics from a system level is crucial to meet practical applications. Summary of the invention
[0011] In view of the shortcomings of the prior art, the object of the present invention is to provide a composite diaphragm for a solid-state lithium-ion battery and a preparation method thereof and a solid-state lithium-ion battery. The composite diaphragm provided by the present invention is used in a solid-state lithium-ion battery to increase the energy density of the battery while reducing the battery impedance and increasing the cycle life of the battery.
[0012] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0013] In a first aspect, the present invention provides a composite diaphragm for a solid-state lithium-ion battery, wherein the composite diaphragm for a solid-state lithium-ion battery comprises a first coating layer, a first base film layer, an intermediate lithium layer, a second base film layer, and a second coating layer stacked in sequence;
[0014] The first coating layer faces the positive electrode side, and the first coating layer includes a first lithium-containing material;
[0015] The second coating layer faces the negative electrode side, and the second coating layer includes a second lithium-containing material.
[0016] The composite diaphragm provided by the present invention comprises a first coating layer and a second coating layer facing the positive electrode side and the negative electrode side, which contain a lithium-containing material, and on the one hand, can supplement the irreversible initial capacity loss of the electrode active material, thereby improving the energy density of the battery, and can also effectively isolate moisture; on the other hand, the first lithium-containing material and the second lithium-containing material can be used as lithium salts in the electrolyte of the solid-state lithium-ion battery to realize the function of ion transmission; at the same time, the intermediate lithium layer can supplement the irreversible lithium loss of the negative electrode active material and the SEI lithium loss, thereby improving the energy density and cycle stability of the battery; the first base film and the second base film, on the one hand, separate the first coating layer and the second coating layer from the intermediate lithium layer, and on the other hand, also play a supporting role; the composite diaphragm is used in a solid-state lithium-ion battery, which can reduce the battery impedance and improve the cycle life of the battery while improving the battery energy density.
[0017] In the present invention, each structural layer in the composite diaphragm is indispensable, and the stacking order must be coordinated. Without any structural layer, it is impossible to effectively improve the battery energy density, reduce the battery impedance, increase the battery cycle life and improve the battery safety. For example, if the second coating is missing, the interface solidification cannot be achieved, the continuous growth of SEI cannot be inhibited, and the technical problem of lithium loss cannot be solved, thereby resulting in continuous impedance growth and capacity attenuation during the cycle; for another example; if the intermediate lithium layer is missing, the irreversible lithium loss caused by the initial low efficiency of the negative electrode cannot be supplemented, thereby reducing the energy density of the battery; if the first coating is missing, the efficient lithium supplementation on the positive electrode side cannot be achieved, thereby reducing the battery energy density. However, if the stacking sequence is adjusted, it is impossible to achieve the improvement of battery energy density, the reduction of impedance, the improvement of cycle life and the improvement of safety. For example, if the position of the intermediate lithium layer is swapped with the first coating or the second coating, the lithium layer close to the positive electrode side or the negative electrode side will be exposed to the atmosphere, and will be quickly passivated, and non-conductive substances such as lithium carbonate will be formed on the surface. When encountering moisture and high temperature environment, it is easy to catch fire and burn, and safety problems will arise; similarly, if the position of the first coating and the second coating is swapped, the lithium replenishment effect on the positive electrode side and the in-situ curing function on the negative electrode side cannot be achieved, thereby reducing battery safety and battery energy density. Furthermore, if neither the first coating nor the second coating contains lithium-containing materials, the in-situ curing function of the composite diaphragm cannot be achieved, and the rapid transmission of ions cannot be achieved, thereby reducing the safety of the battery.
[0018] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0019] Preferably, the first lithium-containing material comprises an inorganic lithium ion conductor material and / or a positive electrode lithium supplement material.
[0020] In the present invention, when the first coating layer includes both the inorganic lithium ion conductor material and the positive electrode lithium replenishing material, the positive electrode lithium replenishing effect can be achieved, and the inorganic lithium ion conductor material can effectively isolate moisture and ensure the air stability of the lithium replenishing agent; and the structural relationship between the inorganic lithium ion conductor and the positive electrode lithium replenishing agent is a composite form, and the inorganic lithium ion conductor is wrapped on the surface of the positive electrode lithium replenishing material in the form of a nano-coating layer.
[0021] It should be noted that the material types of the inorganic lithium ion conductor material and the positive electrode lithium supplement material provided by the present invention are selected according to conventional technology;
[0022] Specifically, the inorganic lithium ion conductor material includes but is not limited to at least one of lithium lanthanum zirconium oxide (LLZO), lithium lanthanum titanate (LLTO), lithium titanium phosphate (LTP), lithium aluminum titanium phosphate (LATP), lithium aluminum germanium phosphate (LAGP), lithium aluminate (LAO, i.e. LiAlO2), tantalum-doped lithium lanthanum zirconium oxide (LLZTO), niobium-doped lithium lanthanum zirconium oxide (LLZNO), lithium germanium phosphorus sulfur (LGPS) or Li2S-P2S5-based sulfide (LPS);
[0023] Specifically, the positive electrode lithium supplement material includes but is not limited to Li2M1O2, Li2M2O3, Li5Fe x M3 (1-x) O4 or Li6MnyM4 (1-y) O4; wherein, M1 includes at least one of Ni, Mn, Cu, Fe, Cr and Mo, M2 includes at least one of Ni, Mn, Fe, Mo, Zr, Si, Cu, Cr and Ru, M3 includes at least one of Al, Nb, Co, Mn, Ni, Mo, Ru and Cr, and M4 includes at least one of Ni, Fe, Cu and Ru; 0≤x≤1, 0≤y≤1.
[0024] Further preferably, in the first lithium-containing material, the mass ratio of the inorganic lithium ion conductor material to the positive electrode lithium supplement material is 1:(10~100), for example 1:10, 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90, 1:100, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] Preferably, the thickness of the first coating is less than 5 μm, for example 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 4.9 μm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0026] Preferably, the second lithium-containing material comprises an inorganic lithium ion conductor material.
[0027] In the present invention, the inorganic lithium ion conductor material in the second coating facing the negative electrode side improves the thermal stability, mechanical strength, puncture resistance, liquid retention, ion transmission characteristics and compatibility with the negative electrode material of the composite diaphragm, and the material type of the inorganic lithium ion conductor material in the second lithium-containing material is also selected by conventional technology, and technical personnel in this field can make adaptive selections and adjustments based on actual needs.
[0028] Preferably, the particle size D50 of the second lithium-containing material is less than 200 nm, for example 50 nm, 80 nm, 100 nm, 130 nm, 150 nm, 180 nm or 190 nm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] In the present invention, the particle size D50 of the second lithium-containing material is less than 200 nm, which can shorten the ion transmission path, increase the specific surface area, increase the electrochemical reaction active sites, accelerate the curing reaction process, and form a denser solidified layer.
[0030] Preferably, the thickness of the second coating is less than 5 μm, for example 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 4.9 μm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] Preferably, the intermediate lithium layer comprises a metallic lithium layer, and the thickness of the intermediate lithium layer is less than 3 μm, for example 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm or 2.9 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0032] It should be noted that the thickness of the first base film layer and the second base film layer in the present invention may be consistent or inconsistent. Specifically, the thickness of the first base film layer and the second base film layer are each independently 0.5μm~10μm, for example, 0.5μm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm or 9μm, etc.
[0033] In a second aspect, the present invention provides a method for preparing a composite diaphragm for a solid-state lithium-ion battery as described in the first aspect, the preparation method comprising the following steps:
[0034] The first coating layer, the first base film layer, the intermediate lithium layer, the second base film layer and the second coating layer are composited to obtain the composite diaphragm for the solid-state lithium ion battery.
[0035] In the preparation method of the composite diaphragm provided by the present invention, the preparation process of each structural layer is not particularly limited, and the present invention is applicable to any preparation method of a specific structural layer; the composite method is also a conventional technical solution.
[0036] Optionally, the preparation method of the first coating includes: (1) coating pretreatment: select a positive electrode lithium replenishing material coated with a nano inorganic lithium ion conductor and an oleophilic surface agent, and perform pretreatment to make the surface of the positive electrode lithium replenishing material have an oleophilic property; (2) coating slurry preparation: select a positive electrode lithium replenishing material coated with a nano inorganic lithium ion conductor that has been treated with oiliness, a binder, a conductive agent, and an organic solvent, perform a mixing treatment, control parameters such as solid content and slurry viscosity, and stir to obtain a coating slurry; (3) base film pretreatment: use a solvent or a detergent to clean the diaphragm substrate (first base film layer) to ensure that the surface is clean and free of debris and pollutants. (4) coating: place the cleaned base film on the coating equipment, and evenly coat the coating slurry on the base film by spraying, rolling, etc.; (5) drying: after coating, send the diaphragm into a drying room or oven, dry it at an appropriate temperature and time, remove the residual solvent, and obtain a composite film with a first coating (first coating and first base film layer);
[0037] Optionally, the first base film layer and the second base film layer can be purchased directly, or can be prepared by conventional preparation methods, such as electrospinning, phase conversion, template method, and 3D printing technology;
[0038] Optionally, the preparation method of the intermediate lithium layer includes: vacuum evaporation method, sputtering method, electrochemical deposition method, sol-gel method, extrusion method;
[0039] Optionally, the preparation method of the second coating layer includes: roller coating, spray coating, brush coating, and dip coating;
[0040] Furthermore, in the composite diaphragm, the composite methods of the various structural layers include: co-extrusion method, coating composite method, lamination composite method or stretching composite method, etc.
[0041] In a third aspect, the present invention further provides a solid-state lithium-ion battery, the solid-state lithium-ion battery comprising a positive electrode sheet, a negative electrode sheet, the composite separator as described in the first aspect, and an electrolyte;
[0042] The added raw materials of the electrolyte include an organic solvent and a curing agent.
[0043] In the present invention, in addition to the organic solvent, a curing agent is additionally added to the raw materials for adding the electrolyte. The curing agent realizes the in-situ solidification of the organic solvent in the electrolyte in the composite diaphragm (the organic solvent is fully solidified or partially solidified), and cooperates with the first lithium-containing material and the second lithium-containing material in the composite diaphragm to realize the in-situ solidification of the liquid electrolyte (organic solvent) in the positive and negative electrode sheets and the isolation membrane, reduce the fluidity of the electrolyte, improve the safety and cycle life of the battery, thereby reducing the battery impedance while improving the battery energy density, and improving the battery cycle life and rate performance.
[0044] Preferably, the organic solvent includes a chain ester compound, and the mass proportion of the chain ester compound in the organic solvent is ≥1 / 3, for example, 1 / 3, 0.4, 0.5, 0.6, 0.7, 0.8 or 0.9, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0045] Preferably, the organic solvent also includes cyclic ester compounds, and the mass proportion of the cyclic ester compounds in the organic solvent is ≥1 / 3, for example, 1 / 3, 0.4, 0.5, 0.6, 0.7, 0.8 or 0.9, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0046] Preferably, the curing agent includes a hydrocarbon compound containing an unsaturated bond, and the amount of the curing agent added is 1% to 5%, for example, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] It should be noted that the present invention does not specifically limit the selection of specific substance types of chain ester compounds, cyclic ester compounds and hydrocarbon compounds containing unsaturated bonds. The present invention is applicable to any substance type that can be used as a solvent in the electrolyte and can achieve a curing effect without affecting the normal performance of the battery.
[0048] Specifically, the chain ester compound includes but is not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC) or ethyl methyl carbonate (EMC);
[0049] Specifically, the cyclic ester compounds include but are not limited to ethylene carbonate (EC) and / or propylene carbonate (PC);
[0050] Specifically, the organic compound containing an unsaturated bond includes, but is not limited to, at least one of olefins, 4-vinyl-1,3-dioxolane-2-one, dibenzoyl peroxide, lithium bis(trifluoromethylsulfonyl)imide, or polyethylene oxide;
[0051] In the present invention, the addition of chain ester compounds to the raw materials of the electrolyte is beneficial to reducing viscosity, improving solubility, and can better achieve similar compatibility with hydrocarbon compounds containing unsaturated bonds; and by further adjusting the ester ratio of chain ester compounds and cyclic ester compounds in the organic solvent, the viscosity, thermal stability and conductivity of the electrolyte can be regulated, thereby improving the safety and rate characteristics of the battery.
[0052] Preferably, the positive electrode active material layer of the positive electrode plate includes a first electron-ion mixed conductor additive.
[0053] In the present invention, adding a first electron ion mixed conductor additive to the positive electrode active material layer can improve the ion transport characteristics of the material and enhance the rate characteristics of the battery; it should also be noted that the present invention does not specifically limit the specific material type of the first electron ion mixed conductor additive, and the present invention is applicable to all types of additives that can achieve electron ion transport, including but not limited to at least one of lithium titanium phosphate, lithium germanium phosphate or lithium lanthanum titanate.
[0054] Preferably, the particle size D50 of the first electronic ion mixed conductor additive is less than 200 nm, for example 50 nm, 80 nm, 100 nm, 130 nm, 150 nm, 180 nm or 190 nm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0055] Preferably, the mass proportion of the first electronic ion mixed conductor additive in the positive electrode active material layer is ≤4%, for example 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.3%, 1.5%, 1.8%, 2%, 2.3%, 2.5%, 2.8%, 3%, 3.3%, 3.5%, 3.8% or 3.9%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0056] Preferably, the negative electrode active material layer of the negative electrode plate includes a second electron-ion mixed conductor additive.
[0057] In the present invention, the negative electrode active material layer includes a second electron ion mixed conductor additive, which is more conducive to achieving in-situ solidification; similarly, the present invention does not specifically limit the specific material type of the second electron ion mixed conductor additive, and the present invention is applicable to any type of additive that can achieve electron ion transmission, including but not limited to at least one of lithium titanium phosphate or lithium lanthanum titanate.
[0058] Preferably, the particle size D50 of the second electronic ion mixed conductor additive is less than 200 nm, for example 50 nm, 80 nm, 100 nm, 130 nm, 150 nm, 180 nm or 190 nm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0059] Preferably, the mass proportion of the second electronic ion mixed conductor additive in the negative electrode active material layer is ≤3%, for example 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.3%, 1.5%, 1.8%, 2%, 2.3%, 2.5%, 2.8% or 2.9%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0060] Preferably, the negative electrode active material layer includes silicon-based negative electrode active material.
[0061] Preferably, the mass proportion of the silicon-based negative electrode active material in the negative electrode active material layer is 20%~50%, for example, 20%, 25%, 30%, 35%, 40%, 45% or 50%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0062] Preferably, the negative electrode current collector in the negative electrode plate is a porous structure.
[0063] In the present invention, a pore structure is introduced into the negative electrode current collector, which can improve the bonding strength between the negative electrode active material layer and the current collector, while reducing the mass of the inactive components, thereby improving the battery energy density and cycle stability; a copper foil structure with a porous structure can be directly selected, or conventional pore-forming treatment can be performed on the surface of the negative electrode current collector to obtain a conventional preparation method for a current collector with a porous structure, and the present invention is applicable to both.
[0064] It is understood that, except for the above-mentioned special requirements, the various structures, preparation materials and preparation methods of the solid-state lithium-ion battery in the present invention are all selected according to conventional technologies;
[0065] The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer located on at least one side of the positive electrode current collector; the positive electrode active material layer comprises a positive electrode active material, a first electronic ion mixed conductor additive (optional), a conductive agent and a binder;
[0066] The negative electrode plate comprises a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector; the negative electrode active material layer comprises a negative electrode active material, a second electron ion mixed conductor additive (optional), a conductive agent and a binder.
[0067] Specifically, the positive electrode active material is a compound capable of reversibly inserting and deinserting lithium, specifically, it may include a lithium transition metal composite oxide, a phosphate containing lithium and at least one transition metal selected from the group consisting of nickel, cobalt, manganese and aluminum; further, it may include lithium and a transition metal such as nickel, cobalt or manganese;
[0068] The negative electrode active material includes but is not limited to graphite, soft carbon, hard carbon, silicon oxygen or silicon carbon, etc.;
[0069] The positive electrode binder is used to bind the components such as active materials, conductive materials and current collectors together, and may include at least one selected from the group consisting of polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, styrene-butadiene rubber and fluororubber, preferably polyvinylidene fluoride;
[0070] The conductive agent is mainly used to assist and improve the conductivity in the secondary battery, and there is no particular limitation as long as it has conductivity without causing chemical changes. The conductive agent may include graphite, such as natural graphite or artificial graphite; carbon materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black; conductive fibers, such as carbon fibers and metal fibers; conductive tubes, such as carbon nanotubes; metal powders, such as fluorocarbon powders, aluminum powders and nickel powders; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; and polyphenylene derivatives.
[0071] Compared with the prior art, the present invention has the following beneficial effects:
[0072] (1) The composite diaphragm provided by the present invention comprises a first coating layer and a second coating layer facing the positive electrode side and the negative electrode side, which contain a lithium-containing material. On the one hand, the first coating layer and the second coating layer can supplement the irreversible initial capacity loss of the active material of the positive electrode sheet, thereby improving the energy density of the battery, and can also effectively isolate moisture. On the other hand, the first lithium-containing material and the second lithium-containing material can be used as lithium salts in the electrolyte of the solid-state lithium-ion battery to realize the function of ion transmission. At the same time, the intermediate lithium layer can supplement the irreversible lithium loss of the active material of the negative electrode sheet and supplement the SEI lithium loss, thereby improving the energy density and cycle stability of the battery. On the one hand, the first base film and the second base film separate the first coating layer and the second coating layer from the intermediate lithium layer, and on the other hand, they also play a supporting role. The composite diaphragm is used in a solid-state lithium-ion battery to improve the energy density of the battery while reducing the battery impedance and improving the cycle life of the battery.
[0073] (2) In the present invention, in addition to the organic solvent, a curing agent is additionally added to the raw materials for adding the electrolyte. The curing agent realizes the in-situ solidification of the organic solvent in the electrolyte in the composite separator (the organic solvent is fully solidified or partially solidified), and cooperates with the first lithium-containing material and the second lithium-containing material in the composite separator to realize the in-situ solidification of the liquid electrolyte (organic solvent) in the positive and negative electrode sheets and the separator, reduce the fluidity of the electrolyte, improve the safety and cycle life of the battery, thereby reducing the battery impedance while improving the battery energy density, and improving the battery cycle life and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0074] Figure 1 This is an SEM image of the surface structure of the composite membrane provided in Application Example 1 before the second coating cycle near the negative electrode side.
[0075] Figure 2 This is the surface structure SEM of the composite membrane provided in Application Example 1 after the second coating cycle near the negative electrode side. DETAILED DESCRIPTION
[0076] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0077] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions.
[0078] In the description of this application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of this application, the meaning of "plurality" is more than two, unless otherwise clearly and specifically defined.
[0079] Example 1
[0080] This embodiment provides a composite diaphragm, the composite diaphragm comprising a first coating layer, a first base film layer, an intermediate lithium layer, a second base film layer and a second coating layer stacked in sequence;
[0081] The thickness of the first coating layer is 4 μm. The first coating layer includes a first lithium-containing material, wherein the first lithium-containing material is coated with a nano inorganic lithium ion conductor (Li 1.3 Al 0.3 Ti 1.7(PO4)3, LATP) positive electrode lithium supplement material (Li5FeO4), binder and conductive agent;
[0082] The thickness of the middle lithium layer is 2 μm;
[0083] The second coating layer includes (a second lithium-containing material Li 0.3 La 0.56 TiO3, D50 is 180nm) and a binder and a conductive agent, the thickness of the second coating is 2μm.
[0084] The preparation method of the composite diaphragm is as follows:
[0085] (1) Basement membrane preparation and pretreatment
[0086] Using an electrospinning method, a PP-based first base film (thickness of 5 μm) is prepared; using a solvent or a detergent to clean the diaphragm substrate;
[0087] (2) Preparation of the first coating
[0088] a) Coating pretreatment: Select the first lithium-containing material (coated with nano inorganic lithium ion conductor Li 1.3 Al 0.3 Ti 1.7 (PO4)3 positive electrode lithium supplement material Li5FeO4), the coating amount of inorganic lithium ion conductor is 2%), and lipophilic surface reagent (sodium alkyl sulfonate) is pretreated;
[0089] b) Preparation of coating slurry: Select the first lithium-containing material after oil treatment, a binder (polyvinylidene fluoride PVDF), a conductive agent (conductive carbon black), and an organic solvent (N-methylpyrrolidone NMP), and mix them, wherein the mass percentage of the first lithium-containing material, the binder, and the conductive agent is 94%:3%:3%, the solid content is controlled to be 50%-55%, and the slurry viscosity is 5500-7500mpa·s, and stir evenly to obtain a coating slurry;
[0090] c) coating: placing the cleaned first base film on a coating device, and uniformly coating the coating slurry on one surface of the base film by roller coating;
[0091] d) Drying: After coating, the membrane is placed in an oven to dry and remove the residual solvent to obtain a composite membrane with the first coating;
[0092] (3) Preparation of intermediate lithium layer
[0093] The single lithium is squeezed onto the other surface of the PP-based first base film by an extrusion method;
[0094] (4) Preparation of the second coating
[0095] a) Coating pretreatment: Select the second lithium-containing material and the lipophilic surface reagent (sodium alkyl sulfonate) for pretreatment;
[0096] b) Preparation of coating slurry: Select the second lithium-containing material treated with oil, a binder (polyvinylidene fluoride PVDF), a conductive agent (conductive carbon black), and an organic solvent (N-methylpyrrolidone NMP), and mix them, wherein the mass percentage of the second lithium-containing material, the binder, and the conductive agent is 96%:2%:2%, the solid content is controlled to be 55%-65%, and the slurry viscosity is 6000-8000mpa·s, and stir evenly to obtain a coating slurry;
[0097] c) coating: placing the cleaned second base film on a coating device, and uniformly coating the coating slurry on one surface of the base film by roller coating;
[0098] d) Drying: After coating, the membrane is placed in an oven to dry and remove the residual solvent to obtain a composite membrane with a second coating;
[0099] (5) Composite diaphragm preparation
[0100] A lamination composite method is adopted to composite a PP-based first base film covered with a single-substance lithium layer and a first coating material and a PE-based second base film coated with a second coating material, wherein the single-substance lithium layer is located in the middle layer of the PP and PE base films; thereby a composite diaphragm is obtained.
[0101] Example 2
[0102] This embodiment provides a composite diaphragm, the composite diaphragm comprising a first coating layer, a first base film layer, an intermediate lithium layer, a second base film layer and a second coating layer stacked in sequence;
[0103] The thickness of the first coating layer is 3 μm, and the first coating layer includes a first lithium-containing material (coated with a nano inorganic lithium ion conductor (Li7La3Zr2O 12 , LLZO) positive electrode lithium supplement material (Li2NiO2)), binder and conductive agent;
[0104] The thickness of the middle lithium layer is 1 μm;
[0105] The second coating includes Li 0.3 La 0.56 TiO3 (the second lithium-containing material, D50 is 180 nm), a binder and a conductive agent, and the thickness of the second coating layer is 2 μm.
[0106] The rest of the preparation methods and parameters were the same as those in Example 1.
[0107] Example 3
[0108] The difference between this embodiment and embodiment 1 is that the first lithium-containing material in the first coating of this embodiment is a nano inorganic lithium ion conductor LATP, and does not contain a positive electrode lithium supplement material.
[0109] The rest of the preparation methods and parameters were the same as those in Example 1.
[0110] Example 4
[0111] The difference between this embodiment and embodiment 1 is that the first lithium-containing material in the first coating of this embodiment is the positive electrode lithium supplement material Li5FeO4, and does not contain nano inorganic lithium ion conductor.
[0112] The rest of the preparation methods and parameters were the same as those in Example 1.
[0113] Example 5
[0114] The difference between this embodiment and embodiment 1 is that the D50 of the second lithium-containing material in the second coating layer of this embodiment is 500 nm.
[0115] The rest of the preparation methods and parameters were the same as those in Example 1.
[0116] Comparative Example 1
[0117] The difference between this comparative example and Example 1 is that the composite diaphragm provided in this comparative example does not contain the first coating;
[0118] In the preparation method, the preparation of the first coating layer is not performed.
[0119] The structure, stacking sequence, preparation method and parameters of the remaining composite membranes are consistent with those in Example 1.
[0120] Comparative Example 2
[0121] The difference between this comparative example and Example 1 is that the first coating layer of the composite diaphragm provided in this comparative example does not contain the first lithium-containing material.
[0122] In the preparation method, the first lithium-containing material is not added.
[0123] The structure, stacking sequence, preparation method and parameters of the remaining composite membranes are consistent with those in Example 1.
[0124] Comparative Example 3
[0125] The difference between this comparative example and Example 1 is that the composite separator provided in this comparative example does not contain an intermediate lithium layer;
[0126] In the preparation method, no intermediate lithium layer is prepared.
[0127] The structure, stacking sequence, preparation method and parameters of the remaining composite membranes are consistent with those in Example 1.
[0128] Comparative Example 4
[0129] The difference between this comparative example and Example 1 is that the composite diaphragm provided in this comparative example does not contain a second coating;
[0130] In the preparation method, the second coating layer is not prepared.
[0131] The structure, stacking sequence, preparation method and parameters of the remaining composite membranes are consistent with those in Example 1.
[0132] Comparative Example 5
[0133] The difference between this comparative example and Example 1 is that the second coating layer of the composite diaphragm provided in this comparative example does not contain the second lithium-containing material.
[0134] In the preparation method, the second lithium-containing material is not added.
[0135] The structure, stacking sequence, preparation method and parameters of the remaining composite membranes are consistent with those in Example 1.
[0136] Comparative Example 6
[0137] The difference between this comparative example and Example 1 is that in this comparative example, the positions of the first coating layer and the second coating layer in the composite diaphragm are exchanged.
[0138] The structure, stacking sequence, preparation method and parameters of the remaining composite membranes are consistent with those in Example 1.
[0139] Comparative Example 7
[0140] This comparative example provides a PP base film as a diaphragm structure.
[0141] Application Example 1
[0142] This application example provides a solid-state lithium-ion battery, which includes a positive electrode sheet, a negative electrode sheet, the composite separator provided in Example 1, and an electrolyte, wherein the raw materials of the electrolyte include an organic solvent and a curing agent;
[0143] The preparation method of the solid-state lithium-ion battery is as follows:
[0144] (1) Preparation of positive electrode
[0145] High voltage lithium cobalt oxide is used as the positive electrode active material, carbon black is used as the conductive agent, PVDF is used as the binder, and LiTi2(PO4)3 is used as the electronic ion mixed conductive agent. The mass ratio of the positive electrode active material, the conductive agent, the binder, and the electronic ion mixed conductive agent is 95:1.5:1.5:2. NMP is used as the solvent to prepare the positive electrode slurry, and the solid content is controlled to be 65%~70%. 12μm aluminum foil is used as the positive electrode current collector, and the positive electrode sheet is prepared by coating and drying.
[0146] (2) Negative electrode preparation
[0147] A silicon-carbon negative electrode (silicon content of 25%) is used as the negative electrode active material, carbon black is used as the conductive agent, CMC / SBR mixed emulsion is used as the binder, and LiTi2(PO4)3 is used as the electronic ion mixed conductive agent. The mass ratio of the negative electrode active material, the conductive agent, the binder, and the electronic ion mixed conductive agent is 94:2:2:2. Water is used as the solvent to prepare the negative electrode slurry, and the solid content is controlled to be 50%-60%. A 6μm porous copper foil is used as the negative electrode current collector, and the negative electrode sheet is prepared by coating and drying.
[0148] (3) Composite diaphragm preparation
[0149] The composite diaphragm in Example 1 is used as the isolation membrane;
[0150] (4) Preparation of electrolyte
[0151] EC / DEC / EMC (mass ratio of 1:1:1) is used as the electrolyte solvent; a mixture of 4-vinyl-1,3-dioxolane-2-one, dibenzoyl peroxide, lithium bis(trifluoromethylsulfonyl)imide and polyethylene oxide is used as the curing agent, wherein the mass percentage of the curing agent is 3% of the raw materials of the electrolyte.
[0152] (5) Battery equipment
[0153] According to the method of GB / T 39861, a soft-pack battery with a capacity of 2000mAh is prepared. The temperature in the formation stage is controlled at 45±1℃, and the curing agent is cured in situ during the first discharge process.
[0154] Application Example 2-5
[0155] The difference between Application Examples 2-5 and Application Example 1 is that the composite diaphragms provided in Examples 2-5 are respectively used as the diaphragm structures.
[0156] The structure and preparation process of the remaining batteries are consistent with those of Application Example 1.
[0157] Application Example 6
[0158] The difference between this application example and application example 1 is that the raw materials of the electrolyte in this application example do not contain EMC and DEC (that is, do not contain chain ester compounds), but only EC. The rest of the battery structure and preparation process are consistent with those in application example 1.
[0159] Application Example 7
[0160] The difference between this application example and application example 1 is that in the raw materials of the electrolyte of this application example, the mass ratio of EC, DEC and EMC is 6:1:1, that is, the mass proportion of the chain ester compound in the organic solvent is 1 / 4.
[0161] The structure and preparation process of the remaining batteries are consistent with those of Application Example 1.
[0162] Comparative Application Examples 1-7
[0163] The difference between comparative application examples 1-7 and application example 1 is that the composite diaphragms provided in comparative examples 1-7 are respectively used as the diaphragm structure.
[0164] The structure and preparation process of the remaining batteries are consistent with those of Application Example 1.
[0165] The batteries provided in Application Examples 1-7 and Comparative Application Examples 1-7 were subjected to performance tests, including tests on discharge specific capacity, rate, average operating voltage, DC internal resistance and cycle performance. The test conditions were:
[0166] a) Discharge specific capacity: 0.2C / 0.2C, 2.8V-4.45V;
[0167] b) Rate: 0.2C / 1C, 2.8V-4.45V;
[0168] c) Average operating voltage: 0.2C / 0.2C, 2.8V-4.45V;
[0169] d) DC internal resistance: 50% SOC 1C pulse 10s;
[0170] e) Cycle life: 0.5C / 1C, 2.8V-4.45V, 50 cycles;
[0171] Figure 1 The SEM image of the surface structure of the composite membrane provided in Application Example 1 before the second coating cycle near the negative electrode side is shown.
[0172] Figure 2 The surface structure SEM of the composite separator provided in Application Example 1 after the second coating cycle near the negative electrode side is shown.
[0173] from Figure 1 and Figure 2 It can be seen that after cycling, the coating surface of the composite diaphragm of the solid-state battery prepared using the composite diaphragm provided by the present invention is transformed from discrete particles into a dense solidified film. The electrolyte membrane effectively inhibits the continuous generation and decomposition of the negative electrode SEI film and the loss of active lithium, greatly improving the cycle life of the battery.
[0174] The test results of the above tests are shown in Table 1.
[0175] Table 1
[0176]
[0177] From Table 1, we can get:
[0178] From the data results of application examples 1-7, it can be seen that the composite diaphragm structure provided by the present invention cooperates with a specific electrolyte raw material with a curing agent, and after being used in a solid-state battery, after formation and curing, the first discharge specific capacity, rate, average operating voltage, DC internal resistance and cycle life of the battery are all improved;
[0179] From the data results of Application Examples 1 and Application Examples 3-5, it can be seen that the electrochemical performance of the solid battery can be better improved by further regulating the type of the first lithium-containing material in the first coating in the composite diaphragm structure, or regulating the D50 of the second lithium-containing material in the second coating;
[0180] From the data results of Application Examples 1, 6 and 7, it can be seen that the chain ester compounds and cyclic ester compounds in the raw materials of the electrolyte can cooperate to better improve the electrochemical performance of the solid battery;
[0181] From the data results of Application Example 1 and Comparative Application Examples 1-7, it can be seen that the composite diaphragm provided by the present invention, the various functional layers and the stacking sequence must cooperate with each other and none of them can be dispensable in order to achieve the simultaneous improvement of the first discharge capacity, rate, average operating voltage, DC internal resistance and cycle life of the solid-state battery. If any one of the conditions is missing, the technical effect in Application Example 1 cannot be achieved.
[0182] In summary, the composite diaphragm provided by the present invention contains lithium-containing materials in the first coating layer and the second coating layer facing the positive electrode side and the negative electrode side, which can supplement the irreversible initial capacity loss of the active material of the positive electrode sheet, thereby improving the energy density of the battery, and can also effectively isolate moisture; on the other hand, the first lithium-containing material and the second lithium-containing material can be used as lithium salts in the electrolyte of the solid-state lithium-ion battery to realize the function of ion transmission; at the same time, the intermediate lithium layer can supplement the irreversible lithium loss of the active material of the negative electrode sheet and supplement the SEI lithium loss, thereby improving the energy density and cycle stability of the battery; the first base film and the second base film separate the first coating layer and the second coating layer from the intermediate lithium layer on the one hand, and on the other hand, they also play a supporting role; using the composite diaphragm in a solid-state lithium-ion battery can reduce the battery impedance and improve the cycle life of the battery while improving the battery energy density.
[0183] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A solid-state lithium-ion battery, characterized in that: The solid-state lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet, a composite separator and an electrolyte; the raw materials added to the electrolyte include an organic solvent and a curing agent; the curing agent includes an organic compound containing an unsaturated bond, and the organic compound containing an unsaturated bond includes at least one of olefins, 4-vinyl-1,3-dioxolane-2-one, dibenzoyl peroxide, lithium bis(trifluoromethylsulfonyl)imide or polyethylene oxide; The composite separator for solid-state lithium-ion batteries comprises a first coating layer, a first base film layer, an intermediate lithium layer, a second base film layer and a second coating layer stacked in sequence; The first coating faces the positive electrode side, and the first coating includes a first lithium-containing material; the first lithium-containing material includes an inorganic lithium ion conductor material and a positive electrode lithium supplement material; The second coating layer faces the negative electrode side, and the second coating layer includes a second lithium-containing material; the second lithium-containing material includes an inorganic lithium ion conductor material; The intermediate lithium layer includes a metallic lithium layer.
2. The solid-state lithium-ion battery according to claim 1, characterized in that: The thickness of the first coating layer is less than 5 μm.
3. The solid-state lithium-ion battery according to claim 1 or 2, characterized in that: The particle size D50 of the second lithium-containing material is less than 200 nm; The thickness of the second coating layer is less than 5 μm.
4. The solid-state lithium-ion battery according to claim 1, characterized in that: The thickness of the intermediate lithium layer is less than 3 μm.
5. The solid-state lithium-ion battery according to claim 1, characterized in that: The preparation method of the composite diaphragm comprises the following steps: The first coating layer, the first base film layer, the intermediate lithium layer, the second base film layer and the second coating layer are composited to obtain the composite diaphragm for the solid-state lithium ion battery.
6. The solid-state lithium-ion battery according to claim 1, characterized in that: The organic solvent comprises a chain ester compound, and the mass proportion of the chain ester compound in the organic solvent is ≥ 1 / 3; The organic solvent further comprises a cyclic ester compound, and the mass proportion of the cyclic ester compound in the organic solvent is ≥ 1 / 3; The added amount of the curing agent is 1% to 5%.
7. The solid-state lithium-ion battery according to claim 5, characterized in that: The positive electrode active material layer of the positive electrode plate includes a first electronic ion mixed conductor additive; The particle size D50 of the first electronic ion mixed conductor additive is less than 200 nm; The mass proportion of the first electron ion mixed conductor additive in the positive electrode active material layer is ≤4%.
8. The solid-state lithium-ion battery according to claim 5, characterized in that: The negative electrode active material layer of the negative electrode plate includes a second electron ion mixed conductor additive; The particle size D50 of the second electronic ion mixed conductor additive is less than 200 nm; The mass proportion of the second electron-ion mixed conductor additive in the negative electrode active material layer is ≤3%.
9. The solid-state lithium-ion battery according to claim 8, characterized in that: The negative electrode active material layer includes a silicon-based negative electrode active material; The mass proportion of the silicon-based negative electrode active material in the negative electrode active material layer is 20% to 50%; The negative electrode current collector in the negative electrode plate is a porous structure.
